Green Growth That Works. - Schnaubelt, Teri (Tantor Media, Inc., 2019)
Rapid economic development has been a boon to human well-being. It has lifted millions out of poverty, raised standards of living, and increased life expectancies. But economic development comes at a significant cost to natural capital-the fertile soils, forests, coastal marshes, farmland-that support all life on earth, including our own. Green Growth That Works is the first practical guide to bring together pragmatic finance and policy tools that can make investment in natural capital both attractive and commonplace. The authors present six mechanisms that demonstrate a range of approaches used around the globe to conserve and restore earth's myriad ecosystems, including: government subsidies; regulatory-driven mitigation; voluntary conservation; water funds; market-based transactions; and bilateral and multilateral payments. Through a series of real-world case studies, the book addresses questions such as: How can we channel economic incentives to make conservation and restoration desirable? What approaches have worked best? How can governments, businesses, NGOs, and individuals work together successfully?